Constraining effects on polymer chain relaxation in crosslinked supramolecular dual networks - Feng, Jasper; Allgaier, Jürgen; Kruteva, Margarita; Förster, Stephan; Pyckhout-Hintzen, Wim (Frontiers in Soft Matter, 2023)
Polymer networks containing transient physical and permanent chemical cross-links exhibit unique mechanical properties due to the intrinsic reassociating ability of supramolecular functional groups. Similar to supramolecular gels, these networks allow controlled release of stored energy and can extend the life of polymer networks in practical applications. In this study, we investigated the rheology, dielectric spectroscopy, , stress-strain behavior and dynamic mechanical analysis of networks based on long polybutylene-oxide (PBO) chains functionalized with randomly placed thymine (Thy) side groups. A transient network was formed by proportionally mixing this matrix with short non-entangled linear 1,3,5-diaminotriazine (DAT) head-tail modified PBO chains, exploiting the hetero-complementarity of the DAT-Thy triple hydrogen bond. This transient polymer network was further cross-linked to a dual network via a thiol-ene click reaction to form static covalent bonds. In PBO, the similar polarity of the PBO matrix and the DAT-Thy functional groups ensures that molecular chain motion is not affected by segregation, resulting in a homogeneous polymer phase without microphase-separated functional group domains. Dielectric relaxation spectroscopy was combined with rheology to quantify the relaxation processes of the interconnected polymers and the strength of the DAT-Thy bonding interactions in the melt. The results showed two distinct plateaux in the relaxation modulus due to contributions from hydrogen and permanent bonds. In the case of the dual network, the lifetime of the hydrogen bond was prolonged and a higher activation energy was observed due to the physical cross-link preventing the movement of the long chain.